HUBUNGAN PERSEPSI DAN SIKAP LANSIA DALAM UPAYA PENCEGAHAN PENULARAN COVID-19 DENGAN PENERAPAN PROTOKOL KESEHATAN DI PUSKESMAS PAYUNG SEKAKI - Ayu Lestari; Ririn Muthia Zukhra; Arneliwati Arneliwati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
The increasing of age decreases the physical health of elderly. Unhealthy life style and ignoring the program of preventing the transmission of COVID-19 caused the elderly easy to be infected by deseases due to the COVID-19 pandemic. Generally, the erderly are less concerned to the effort of preventing the transmission of COVID-19 as suggessted by the government. Cross sectional approach was applied in this study. The sample in this study were 98 participants. The sample were taken by using purposive sampling. A questionairre of perception, attitude, and the health protocols implementation during COVID-19 pandemic was used to collect the data. The validity and reliability of the questionniare has been tested. In analyzing the data, the researcher used univariate and bivaiate of chi square test. The result of analysis showed that the majority of elderlies’ perception of efforts to prevent the transmission of COVID-19 was negative or had negative response (67.3%). Furthermore, the attitude of the elderly majority refuses to prevent the transmission of COVID-19 (64.3%). In addition, the majority of erderly did not apply the health protocols implementation (5M) during the pandemic (66.3%). Bivariate analysis showed that the p value is less than 0.05. There is a significant correlation between the perceptions and attitudes of the elderly in the effort to prevent the transmission of COVID-19 with the health protocols implementation with p-values of 0.002 and 0.011 < (0.05). Keywords: Attitude, COVID-19, elderly, health protocols implementation, perceptions.